ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL RELASI DAN FUNGSI DI KELAS VII SMP NEGERI 4 BALAI JAYA - Lestari, Winda; Kartini, Kartini (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2021)
The concept of relations and functions in the school mathematics curriculum was first accepted by students in grade VIII. In evaluating students' understanding of the concept of relations and function material, there are mistakes made by students. Errors that occur can be in the form of misconceptions, principles, and operating errors. This study aims to describe the types of errors in solving the material relations and functions of the VIII grade students of SMP Negeri 4 Balai Jaya in the odd semester of the 2020/2021 school year. This type of research is descriptive-qualitative research, with the test as a data collection instrument. The subjects in this study were 27 students of class VIIIA. The results showed that on average 60% of students made misconceptions, 51% of students made mistakes in principle and 63% of students made operational errors. Students have not been able to present relations correctly using arrow diagrams, Cartesian diagrams and consecutive sets of pairs. Students also still have difficulty distinguishing relations and functions. In the matter of functions, the use of steps in manipulating algebraic calculations carried out by students is not quite right.